The Godfather II - Coppola, Francis Ford.; Paramount Home Video (Hollywood, Calif. Paramount Pictures, 1974)
Continuing saga of the Corleone family as they move to Nevada and make the casino business their major income source under the leadership of the increasingly paranoid and malevolent Michael, whose reign as the 'Don' is juxtaposed against the parallel tale of his father's escape from Sicily as a young boy and his subsequent rise to power in New York's Lower East Side during the turn-of-the-century.
Summary from website: http://www.rottentomatoes.com/m/godfather_part_ii
DVD
Based on the book by Mario Puzo.
Title from container.
Originally released as VHS by Paramount Home Video in March 24, 1972.
Writers: Francis Ford Coppola, Mario Puzo; Producers: Francis Ford Coppola
Marlon Brando, Al Pacino, James Caan, Richard Castellano, Robert Duvall, Diane Keaton, Sterling Hayden
Keywords: Family -- Mystery; Family -- History -- Drama; Casino business -- Nevada -- Action; Family leader -- Family traditions -- Drama; Epic films; Historical films; Biographical films